Parametric optimization of biodiesel synthesis from rubber seed oil using iron doped carbon catalyst by Taguchi approach. (May 2017) - Dhawane, Sumit H.; Bora, Akash Pratim; Kumar, Tarkeshwar; Halder, Gopinath
Abstract: Improvisation of the biodiesel production by employing heterogeneous catalyst and its optimization is the best way to mitigate the growing concern with the traditional feedstocks and their prices. The present study is aimed at optimizing the biodiesel production process and identifying significant parameters affecting the biodiesel yield. The biodiesel is synthesized from rubber seed oil (RSO) using indigenously prepared iron doped catalyst (Fe/C). The optimized condition obtained by maximizing the RSME (Rubber seed oil methyl ester) yield at 97.5% are catalyst loading 4.5 wt%, Methanol/Oil (M/O) 9:1, temperature 60 °C and agitation speed 1250 RPM. The physicochemical properties of RSME produced at optimized condition are found to be within the prescribed limits suggested by ASTM. The contribution factor estimated for individual parameters revealed that temperature, agitation speed, and M/O ratio have a more significant effect on the RSME yield. The reusability of the Fe/C catalyst was also studied to check its activity in the reuse and found to be effective after three cycles with appreciable catalytic activity. Hence, the study reveals RSO could be effective feedstock for the production of biodiesel using novel Fe/C catalyst to produce energy efficient and cost effective RSME towards the production of sustainable energy. Highlights: Indigenous development of carbonaceous heterogeneous catalyst from waste biomass. Experimental design by L9 orthogonal array method by Taguchi approach. Parametric effects of individual parameter on biodiesel yield. Regression and statistical analysis of the biodiesel synthesis process. Produced biodiesel characterized following standard methods.